Long-Term Population Studies Uncover the Genome Structure and Genetic Basis of Xenobiotic and Host Plant Adaptation in the Herbivore Tetranychus urticae. Issue 4 (11th February 2019) - Wybouw, Nicky; Kosterlitz, Olivia; Kurlovs, Andre H; Bajda, Sabina; Greenhalgh, Robert; Snoeck, Simon; Bui, Huyen; Bryon, Astrid; Dermauw, Wannes; Van Leeuwen, Thomas; Clark, Richard M
Abstract: Pesticide resistance arises rapidly in arthropod herbivores, as can host plant adaptation, and both are significant problems in agriculture. These traits have been challenging to study as both are often polygenic and many arthropods are genetically intractable. Here, we examined the genetic architecture of pesticide resistance and host plant adaptation in the two-spotted spider mite, Tetranychus urticae, a global agricultural pest. We show that the short generation time and high fecundity of T. urticae can be readily exploited in experimental evolution designs for high-resolution mapping of quantitative traits. As revealed by selection with spirodiclofen, an acetyl-CoA carboxylase inhibitor, in populations from a cross between a spirodiclofen-resistant and a spirodiclofen-susceptible strain, and which also differed in performance on tomato, we found that a limited number of loci could explain quantitative resistance to this compound. These were resolved to narrow genomic intervals, suggesting specific candidate genes, including acetyl-CoA carboxylase itself, clustered and copy variable cytochrome P450 genes, and NADPH cytochrome P450 reductase, which encodes a redox partner for cytochrome P450s. For performance on tomato, candidate genomic regions for response to selection were distinct from those responding to the synthetic compound and were consistent with a more polygenic architecture. In accomplishing this work, we exploited the continuous nature of allele frequency changes across experimental populations to resolve the existing fragmented T. urticae draft genome to pseudochromosomes. This improved assembly was indispensable for our analyses, as it will be for future research with this model herbivore that is exceptionally amenable to genetic studies.